Impacts of reprocessed altimetry on the surface circulation and variability of the Western Alboran Gyre. Issue 3 (1st August 2016) - Juza, Mélanie; Escudier, Romain; Pascual, Ananda; Pujol, Marie-Isabelle; Taburet, Guillaume; Troupin, Charles; Mourre, Baptiste; Tintoré, Joaquín
Abstract: New altimetry products in semi-enclosed seas are of major interest given the importance of the coastal-open ocean interactions. This study shows how reprocessed altimetry products in the Mediterranean Sea from Archiving, Validation and Interpolation of Satellite Oceanographic data (AVISO) have improved the representation of the surface circulation over the 1993–2012 period. We focus on the Alboran Sea, which is the highest mesoscale activity area of the western Mediterranean. The respective impacts of the new mean dynamic topography (MDT) and mapped sea level anomaly (MSLA) on the description of the Western Alboran Gyre (WAG) are quantitatively evaluated. The temporal mean and variability of the total kinetic energy have been significantly increased in the WAG considering both the new MDT and MSLA (by more than 50%). The new MDT has added 39% to the mean kinetic energy, while the new MSLA has increased the eddy kinetic energy mean (standard deviation) by 53% (30%). The new MSLA has yielded higher variability of total (eddy) kinetic energy, especially in the annual frequency band by a factor of 2 (3). The MDT reprocessing has particularly increased the low-frequency variability of the total kinetic energy by a factor of 2. Geostrophic velocities derived from the altimetry products have also been compared with drifter data. Both reprocessed MDT and MSLA products intensify the velocities of the WAG making them closer to the in situ estimations, reducing the root mean square differences and increasing the correlation for the zonal and meridional components. The results obtained using refined coastal processing of altimetry products and new observational data are very encouraging to better understand the ocean circulation variability and coastal-open ocean interactions, and for potential improvements in other sub-basins, marginal seas and coastal global ocean.